"...but the poor opted for the evangelicals!" - Evangelicals, poverty and prosperity - Gideon van der Watt (Acta Theologica)
This article discusses developments in the historical discourse on evangelicalism, poverty and prosperity. Have the global evangelical celebrations of 2010 bridged the dichotomy between social responsibility (Ecumenicals) and the proclamation of salvation (Evangelicals)? The article focuses on the rapid growth of a specific brand of evangelicalism, namely “prosperity faith” as predisposition within the neo-Pentecostal churches, especially throughout sub-Saharan Africa. In an appreciative, but critical enquiry, this article reflects on the radical claim of dispensing “health and wealth” to the desperately poor. Are proponents of prosperity faith putting forward a credible answer to poverty, a new entrepreneurial and creative evangelical response to the call for social responsibility? Or will the poor ultimately be disillusioned? What challenges are posed to Evangelicals?